Pengaruh Pengetahuan Perbankan Syariah dan Lingkungan Keluarga terhadap Minat Menabung Mahasiswa di Bank Syariah - Eko Dwi Prasetyo; Menik Kurnia Siwi (Universitas Negeri Padang, 2022)
This study aims to see the effect of Islamic banking knowledge and family environment on the interest in saving students of the Faculty of Economics, Padang State University in Islamic banks. The method used in this study is a quantitative method. The data analysis technique used in this research is multiple linear regression analysis. The population in this study were students of the Faculty of Economics, Padang State University. Sampling in this study using purposive sampling technique with a total sample of 96 respondents. Data collection in this study used a questionnaire/ questionnaire method. The results of the study found that; (1) Students' knowledge about Islamic banking has no significant effect on saving interest in students of the Faculty of Economics, Padang State University in Islamic banks, this is seen from the significant value of 0.594 > 0.05. (2) Family environment has a positive and significant effect on saving interest in students of the Faculty of Economics, Padang State University in Islamic banks, this is seen from the significant value of 0.00 < 0.05.Keywords: pengetahuan, lingkungan keluarga, minat menabung